Great saphenous vein diameter at different regions and its relation to reflux - Said I El Mallah (Journal of Medicine in Scientific Research, 2021)
Background Great saphenous vein (GSV) incompetence is involved in most cases of varicose disease. Standard preinterventional assessment is required to decide the treatment modalities. GSV diameter was measured at saphenofemoral junction, proximal thigh, distal thigh, knee, proximal leg, and distal leg. Analysis was done to find at which diameter size the reflux is expected to occur. Patient and methods The study involved 100 limbs from outpatient vascular clinic. GSV diameter was measured at the saphenofemoral junction, the proximal thigh, the distal thigh, below the knee, and mid-leg and correlated with reflux. Results Reflux in the sapheno-femoral junction (SFJ) (group I) occurred at 7.16±2.30 mm, proximal thigh (group II) at 6.60±1.89 mm, distal thigh (group III a) at 6.12±1.63 mm, knee (group III b) at 5.78±1.60 mm, proximal leg (group IV) at 4.61.24 mm, and mid leg (group V) at 3.59±1.16 mm. Conclusion Measurement at six sites revealed higher sensitivity and specificity to predict reflux. GSV diameter correlates with reflux.